1986
DOI: 10.1007/bf00199122
|View full text |Cite
|
Sign up to set email alerts
|

Specific tumoricidal activity of cytotoxic macrophages and cytotoxic lymphocytes

Abstract: The antitumor potency and specificity of syngeneic immune peritoneal exudate cells were tested. Groups of DBA/2 mice were immunized against syngeneic SL2 tumor cells. Then 6 days after the last immunization the antitumor potency, and the specificity of the immunization reaction was tested by injecting groups of the immunized mice with 10(3) to 5 X 10(7) DBA/2 derived L1210, L5178Y, P815 or SL2 tumor cells, and injecting immune peritoneal exudate cells into DBA/2 mice which had been injected 2 h earlier i.p. wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Mice immunized with these P815 tumour cell extracts could not reject the challenge with SL2 cells. These results demonstrate that the induction of protective immunity is specific and is consistent with the specific immunity induced by irradiated SL2 cells [8]. Almost all mice that rejected a challenge with SL2 cells after immunization with crude membranes, soluble fraction or reconstituted membranes were able to reject a sec- (Table 4).…”
Section: Specificity Of the Protective Tumour Immunitysupporting
confidence: 75%
See 1 more Smart Citation
“…Mice immunized with these P815 tumour cell extracts could not reject the challenge with SL2 cells. These results demonstrate that the induction of protective immunity is specific and is consistent with the specific immunity induced by irradiated SL2 cells [8]. Almost all mice that rejected a challenge with SL2 cells after immunization with crude membranes, soluble fraction or reconstituted membranes were able to reject a sec- (Table 4).…”
Section: Specificity Of the Protective Tumour Immunitysupporting
confidence: 75%
“…About 50% of the mice immunized s. c. or i.p. with two or three immunization injections with 107 irradiated SL2 cells can resist a lethal challenge with 106 SL2 cells [8,24]. The antigenically unrelated P815 mastocytoma (also DBA/2-derived) was used in specificity studies.…”
Section: Methodsmentioning
confidence: 99%
“…Supportive for the determination of which of the two factors, MAF or SMAF, is responsible for the induction of macrophage cytotoxicity is the finding that the cytotoxic macrophages are tumor specific in this tumor system [9]. MAF-induced macrophage cytotoxicity is nonspecific whereas SMAF-induced macrophage cytotoxicity is tumor specific in this system [8].…”
Section: Discussionmentioning
confidence: 99%
“…In order to activate and/or augment induction of antitumor cells in vivo, several trials have been reported; these include infusion of alloactivated-helper lymphocytes [1,18], active immunizations with tumor vaccines [3,4,28,35] combined with nonspecific immunopotentiators [22,31] or with cyclophosphamide [27], injection of cytokines such as interleukin-2 [14,34], and so on. Our previous report [21] shows that treatment with mitomycin-C-treated EL4 cells (EL4MMC) plus OK-432 (a streptococcal preparation) induces antitumor cells in the treated site, a local site but not in other sites, a systemic site such as the spleen, and slight antitumor resistance in the host receiving the treatment.…”
Section: Introductionmentioning
confidence: 99%